The effectiveness of using films in the teaching of listening to improve the students learning achievement and enhance the students learning motivation - Nouthaphone, Thiphachanh; Purbani, Widyastuti (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
This research study was aimed (1) to investigate the difference in students learning achievement. (2) To investigate the difference in the students learning motivation level. This study was a quasi-experimental design with pretest-posttest control group. The population consisted of all third year students in the second semester of academic 2015/2016 of the English Education Department at Champasack University, Laos consisting of 60 students as the sample. The data were collected using listening comprehension pretest, posttest and a questionnaire for students learning motivation. The data was analyzed by using descriptive statistics and inferential statistics. The result of MANOVA indicated that (1) The students' learning achievement in listening increased significantly after learning with films, F = 4.961 with p = 0.030. (2) The students' learning motivation level increased significantly after they learned with films, F = 5.909 with p = 0.018, which is lower than 0.05. This study found a significant difference in listening achievement and learning motivation levels of the third year students.